2010
DOI: 10.1063/1.3284511
|View full text |Cite
|
Sign up to set email alerts
|

Formation of quantum dots in single stranded DNA-wrapped single-walled carbon nanotubes

Abstract: The transport properties of single-stranded DNA ͑ssDNA͒ wrapped single-walled carbon nanotubes ͑SWNTs͒ are studied from low to room temperature. Atomic force microscopy reveals a regularly patterned geometry of ssDNA molecules on the surface of SWNTs. Our measurements indicate that the semiconducting behavior of SWNTs is drastically changed after ssDNA modification, showing a clear charge-transfer process at room temperature. At low temperatures single-electron tunneling features are observed up to 80 K, demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…To this end, the work [135] has demonstrated that, if one wraps ssDNA around single-walled carbon nanotubes (SWNTs), the semiconducting behavior of latter is drastically changed after ssDNA modification, showing a clear charge-transfer process at room temperature. A further systematic investigation into the temperature dependence of the single-electron tunneling features in this SWNT-ssDNA system has led the authors [135] to a conclusion that it is the ssDNA wrapping around the SWNTs that helps create quantum dots in series.…”
Section: Medical Applications Of Single Molecule Conductancementioning
confidence: 99%
“…To this end, the work [135] has demonstrated that, if one wraps ssDNA around single-walled carbon nanotubes (SWNTs), the semiconducting behavior of latter is drastically changed after ssDNA modification, showing a clear charge-transfer process at room temperature. A further systematic investigation into the temperature dependence of the single-electron tunneling features in this SWNT-ssDNA system has led the authors [135] to a conclusion that it is the ssDNA wrapping around the SWNTs that helps create quantum dots in series.…”
Section: Medical Applications Of Single Molecule Conductancementioning
confidence: 99%
“…This is induced by the transfer of the DNA electrons to the CNT under excitation by the light illumination, and it holds the promise of application development for DNA@CNT organic semiconductors as photoswitching nanobio devices. The formation of quantum dots at low temperatures has also been verified [31], and we are pursuing the possibilities that these unique properties of nanobio-electronics devices endow biosensing and DDS systems with innovative functions.…”
Section: Carbon Nanotube Nanobioelectronicsmentioning
confidence: 94%
“…This was the result of electron transfer in the DNA hybrid molecule with increasing voltage [77]. Other important DNA-based nanoscale devices that have recently been developed include highly conductive nanowires [78], quantum dots with carbon nanotubules [79], and even radically advanced devices which detect single-nucleotide polymorphism and conduct nucleotide sequence mutation analysis [80]. With added progress in this field, it could be possible to use DNA-based electronics for both DNA-based diagnostics and sophisticated nanoscale electrical devices.…”
Section: Reviewmentioning
confidence: 99%